Dinâmica climática, excepcionalidades e vulnerabilidade: contribuições para uma classificação geográfica do clima no estado do Rio de Janeiro - Armond, Núbia Beray (2018)
Rio de Janeiro state has a significant geographic multiplicity, both in terms of its orographic features and climatic diversity, as well as the different patterns of space production in its interior. Faced with this complexity, knowledge about climate elements spatiotemporal variability is fundamental for planning and territorial management purposes. This thesis proposes to carry out a reflection on the climatic classifications in Geography, in order to carry out a geographic analysis of the climate of the State of Rio de Janeiro from the relation between rainfall and vulnerability. It is hypothesized that, although it may have different units of rainfall, rainfall may trigger exceptionalities that are determined by differences in the state's vulnerability patterns. The analytical framework of thesis was based on the perspectives of the geographical climatology, the concept of vulnerability and the Geography of the Climate, proposing an investigation based on the concepts of climatic classification, vulnerability and extreme episodes based on the category of space in its absolute conceptions , relative and relational. In order to do so, we used the climatic data of meteorological stations and pluviometric stations of INMET and ANA rain gauges, with descriptive and multivariate statistical techniques from the fault-filling process to the definition of the standard years for analysis. The cartographic representations were performed with the purpose of demonstrating the inherent complexity of the relationship between the factors and elements of the climate in different scales. The precipitation averages of the analyzed historical series (1975-2015) showed similar patterns to those exhibited by Normal Climatology, with the north and northwest portions of the state showing lower precipitation patterns in relation to the leeward areas of Serra do Mar. to the genesis, more than 90% of the rainfall of the state of Rio de Janeiro comes from the forward movement dynamics of the Atlantic Polar Front (FPA) and / or associated systems (front occlusal, cold front, reflex front and formation of South Atlantic Convergence Zone - ZCAS). Concerning the air masses, the areas near the southern coast, the Serra do Mar and the more continental portions of the state have significant participation of the polar systems (Atlantic polar mass and continentalized Atlantic polar mass - on average 29%), while the areas located in the north of the state of Rio de Janeiro and sectors closer to the coastline, have an average of 35% participation of tropical systems (Atlantic tropical mass, continental Atlantic tropical mass and tropical instability), characterizing the state as belonging to the great transition zone of the Brazilian southeast . Data were also used for flood occurrences (abrupt and gradual) and data referring to the 2010 Census to apply the SoVI - Social Vulnerability Index and to relate this model to extreme episodes. It was verified that, although most of the territory of the state of Rio de Janeiro presents high vulnerability conditions, most occurrences coincided with areas of high and very high vulnerability. However, not necessarily the areas with the highest FPA performance and / or associated systems coincided with the municipalities with the highest number of flood events, which indicates the relevance of an analysis that considers climate dynamics not only in consonance, but in relation to the production dynamics of the geographical space. In summary, it was sought, with this work, to indicate reflections through theoretical argumentation, methodological procedures, analytical arsenal and representation for future proposals of analysis and classification of the climate considering it as an eminently geographical phenomenon, as proposed by Geography of Climate.